Comparison of clinicopathologic and survival characteristics of high grade endometrial cancers; single center experience - (:unkn) unknown (MOSBY-ELSEVIER, 2019)
Purpose: Approximately a quarter of endometrial cancers are of high grade. We aimed to perform clinicopathologic and survival evaluation of high grade endometrial cancer in our study. Method: We evaluated the data of 78 high grade patients; 30 G3EC (Grade 3 Endometrioid Carcinoma), 48 nonendometrioid carcinomas; 32 USC (uterine serous carcinoma), 16 CCC (clear cell carcinoma), from 312 patients who were followed with endometrial cancer between years 2006 and 2016. Results: Mean age was 62 years (range 43-83) in all patients, the age in histologic subtypes was 56.5, 65, 66.3, years for G3EC, USC, and CCC, respectively. The G3EC mean age is significantly smaller than other histologic subtypes (P = 0.00). The median follow-up time was 39 months (range 6-136). The 5-year overall survival was 55%, 44%, G3EC, and nonendometrioid carcinoma (USC and CCC), respectively (P=0.127). In the univariate model; age > 65, ECOG-PS >= 2, stage 3-4 disease, LVI presence were poor prognostic factors (P < 0.05). Effect of the stage of the disease, the age of the patients and ECOG-PS on survival was demonstrated with multivariate analysis. The clinicopathologic features of the patients were similar. Conclusion: G3EC is seen at a younger age than other high grade endometrial carcinomas. Grade 3 endometrioid carcinomas have an increasing trend in survival compared to high grade nonendometrioid carcinomas. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Grade 3 Endometrioid Carcinoma; Uterine Serous Carcinoma; Clear Cell Carcinoma; Nonendometrioid Carcinoma; CLEAR-CELL CARCINOMAS; SEROUS CARCINOMA; CLASSIFICATION